HUBUNGAN SIKAP PROFESI DAN MOTIVASI BERPRESTASI DENGAN KINERJA GURU SD DI KECAMATAN MALILI KABUPATEN LUWU TIMUR - Hardianto Hardianto (Guru Membangun, 2023)
This research is an Ex-Post Facto study which aims to reveal the relationship between the dependent variable (teacher performance) and the independent variable (professional attitude and teacher achievement motivation). The sample in this study were elementary school teachers in the Malili District who were determined by random sampling based on area and proportion. Data collection techniques were carried out using questionnaires. Data analysis used quantitative analysis through descriptive statistics and inferential statistics. The results of the descriptive study show: 1) the description of the attitude of the teaching profession is in the good category with an average score of 91.84; 2) the description of the teacher's achievement motivation is in the good category with an average score of 74.43; and 3) the description of teacher performance is in the very good category with an average score of 94.09. Inferentially, the results of the study show: 1) there is a significant positive relationship between teacher professional attitudes and teacher performance with a correlation of 0.19; 2) there is a significant positive relationship between teacher achievement motivation and teacher performance with a correlation of 0.262; 3) there is a significant positive relationship between teacher professionalism and teacher achievement motivation and teacher performance with a correlation coefficient of 0.285; 4) there is a significant positive relationship between teacher professional attitudes and teacher performance by controlling teacher achievement motivation with a correlation of 0.118; and 5) there is a significant positive relationship between teacher achievement motivation and teacher performance by controlling for the attitude of the teaching profession with a correlation of 0.217